2017
DOI: 10.3989/gya.0800162
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microwave roasting on the yield and composition of cold pressed orange seed oils

Abstract: SUMMARY:The aim of this study was to valorize orange (Citrus sinensis) seeds, which are generated as waste. This study presents data about raw orange seed, the meal gained after cold pressing, and characterization data of the cold pressed seed oils. Furthermore, the effects of microwave roasting of the seds compared to regular roasting (control) were determined. The oil yield of orange seed cold pressing was around 52.93-62.99%. After cold pressing, 13.57-17.97% oil remained in the meal together with 20.68-25.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The protein content of tomato seeds was found to be higher than many different seeds, including chia, safflower, lemon, and orange seeds. [46][47][48][49] As shown in partially in agreement with that of dried tomato pulp. [50] On the other side, Işık and Topkaya (2016) reported 49.86 for Hunter L, 3.38 for a, and 9.95 for b values in dried tomato seeds.…”
Section: Proximate Compositions and Color Of Tomato Seedssupporting
confidence: 79%
See 1 more Smart Citation
“…The protein content of tomato seeds was found to be higher than many different seeds, including chia, safflower, lemon, and orange seeds. [46][47][48][49] As shown in partially in agreement with that of dried tomato pulp. [50] On the other side, Işık and Topkaya (2016) reported 49.86 for Hunter L, 3.38 for a, and 9.95 for b values in dried tomato seeds.…”
Section: Proximate Compositions and Color Of Tomato Seedssupporting
confidence: 79%
“…The protein content of tomato seeds was found to be higher than many different seeds, including chia, safflower, lemon, and orange seeds. [ 46–49 ]…”
Section: Resultsmentioning
confidence: 99%
“…Cold pressed citrus seed oils were previously studied in our laboratory. Lemon seeds (Aydeniz Güneser & Yılmaz, ), orange seeds (Aydeniz Güneser & Yılmaz, ), and grapefruit seeds (Yılmaz, Aydeniz Gneser, & OK, ) were cold pressed, and their oils were characterized in details. It was observed that citrus seed oils were fairly bitter.…”
Section: Introductionmentioning
confidence: 99%
“…Among other processing facilities, cold pressing of seeds and kernels got some attention to produce the so called cold pressed or gourmet oils for various functional food, aroma, nutraceuticals, pharmaceuticals, chemical, and other applications. Since cold pressed oils are natural and not refined, they contain all minor components and bioactive molecules originating from the source material, nonetheless the seeds or kernels should be very clean, safe, and homogeneous …”
Section: Introductionmentioning
confidence: 99%